1997
DOI: 10.1007/bf02450325
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of neuronal firing in the human lateral thalamus during sleep and wakefulness

Abstract: The firing patterns of thalamic neurons in mammals undergo a dramatic change as the animal's state changes between sleep and wakefulness. During sleep the normal tonic firing of thalamic neurons changes into a slower bursting mode characterized by repetitive activation of a low-threshold calcium (Ca2+) current. The present report describes the patterns of thalamic neuronal firing during sleep and wakefulness in one human patient. Extracellular single neuron activity was recorded during functional stereotactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The main reason was that DBS effect is highly dependent on the electrode localization and targets suitable for some pathologies cannot be generally used in other pathologies. In the literature, nevertheless, bursting activity in various thalamic nuclei [ventralis intermediate (VIM), ventralis caudalis (VC), anterior lateral (AL), central lateral (CL)] and in various pathologies (epilepsy, pain, tinnitus, essential tremor, and other abnormal movements) were described and identified as low‐threshold calcium spike bursts 39–43. The results obtained were very close to ours: in essential tremor the interburst interval ranged between 0.17 and 0.39 seconds in the VO and between 0.36 and 0.58 seconds in the VC in awake patients,41 in epilepsy it ranged between 0.172 and 0.361 seconds in the AL in anaesthetized patients,39 in pain and in patients with other abnormal movements ranged between 0.176 and 0.397 seconds in the CL 40.…”
Section: Discussionsupporting
confidence: 78%
“…The main reason was that DBS effect is highly dependent on the electrode localization and targets suitable for some pathologies cannot be generally used in other pathologies. In the literature, nevertheless, bursting activity in various thalamic nuclei [ventralis intermediate (VIM), ventralis caudalis (VC), anterior lateral (AL), central lateral (CL)] and in various pathologies (epilepsy, pain, tinnitus, essential tremor, and other abnormal movements) were described and identified as low‐threshold calcium spike bursts 39–43. The results obtained were very close to ours: in essential tremor the interburst interval ranged between 0.17 and 0.39 seconds in the VO and between 0.36 and 0.58 seconds in the VC in awake patients,41 in epilepsy it ranged between 0.172 and 0.361 seconds in the AL in anaesthetized patients,39 in pain and in patients with other abnormal movements ranged between 0.176 and 0.397 seconds in the CL 40.…”
Section: Discussionsupporting
confidence: 78%
“…4 The thalamus is often considered the gate to the cortex, eg, during wakefulness vs sleep. 43 The transition from wakefulness to sleep leads to a transient functional deafferentation of the cortex, which may share some of its circuitry and neuropharmacology with chronic pain states induced by nerve damage that leads to a more permanent deafferentation. 1 The cortical reorganization observed after amputation 11 is a clinically relevant example of a spatially precise mechanism of gain control in the brain.…”
Section: Gain Control Mechanisms Involving Higher Centers In the Brainmentioning
confidence: 99%
“…Single unit bursts recorded in the thalamic nuclei of patients with neuropathic pain fulfilled the criteria of low-threshold calcium spikes (LTS), i.e. peculiar rhythmic activities reflecting a state of hyperpolarisation and inhibition at the cellular level, similar to that observed during slow wave sleep (LlinĂĄs and Jahnsen, 1982;Lenz et al, 1989;Jeanmonod et al, 1993Jeanmonod et al, , 1994Jeanmonod et al, , 1996Steriade et al, 1993;Tsoukatos et al, 1997;Weng et al, 2003). Furthermore, a direct link between thalamic bursting and reduced metabolic activity was demonstrated by Hirato et al (1994), who obtained both PET-scan and intrathalamic recordings in patients with central post-stroke pain, and showed that the thalamic regions concerned by bursting activity had also reduced glucose metabolism and reduced sensory responses to external stimuli.…”
Section: The Paradox Of Positive Symptoms On the Background Of Decreamentioning
confidence: 99%